Sacred Texts and Jewish Humanoids: Uses of Sacred Texts and Textures When Creating a Golem or Other Artificial Creatures - Schleicher, Marianne (Postscripts: The Journal of Sacred Texts, Cultural Histories, and Contemporary Contexts, 2025)
This article focuses on the human creation of artificial creatures, especially the golem, as a religious phenomenon in early and medieval rabbinic Judaism. Motivated by the scarcity of scholarly reflections on sacred text use as part of golem-related practices, it inquires into the effects of this entanglement on religious identities. A processual, new materialistic understanding of all phenomena and the author’s distinction between hermeneutical and artefactual uses of sacred texts and between sacred texts and sacred textures constitute the article’s theoretical apparatus. The analysis opens by looking at the first usages of the word “golem” in Psalm 139, the Mishnah, and a few early midrashim, connoting matter about to be formed by God and Torah while claiming at the same time insights into divine creation. From here, it turns to two texts associated with the mystical bereshit-tradition: the Babylonian Talmud, tractate Sanhedrin 65b that contains the first description of the human making of an artificial being, and Sefer Yetsirah, a book that also claims insights into divine cosmogonic and anthropogenic processes. In the medieval material, primarily from the context of Ashkenazic piety, the analysis sorts the information on golem-making after a three-year study of Sefer Yetsirah into the tripartite structure of a rite of passage to illustrate the ritual’s transformative effect on the golem-makers’ religious status. The analysis concludes that especially fragmentary renderings of sacred textures are seminal in the golem-makers’ ritual. Had one limited the understanding of sacred text use to a matter of hermeneutics, that is, interpretation proper, one would have overlooked the central sacred text practices that render this anthropogenic ritual an expression of imitatio dei and piety.